Patient-reported outcomes in patients with primary immunodeficiency diseases in Japan: baseline results from a prospective observational study - Kanegane, Hirokazu; Ishimura, Masataka; Kawai, Toshinao; Okada, Satoshi; Okamatsu, Nobuaki; Go, Madoka; Noto, Shinichi (Frontiers in Immunology, 2023)
Introduction: Primary immunodeficiency diseases (PIDs) are rare inherited diseases resulting in impaired immunity. People with PID experience lower health-related quality of life (HR-QOL) and disease-related burdens in daily activities. This ongoing, prospective observational study aims to evaluate disease activity, treatment status, treatment-related burden, daily activities, and HR-QOL in patients with PID in Japan over a 1-year period. In this interim report (database lock: July 29, 2022), we present baseline results. Methods: Participants were enrolled between November 2021 and May 2022; data were collected four times/year per participant until May 2023 using an online electronic patient-reported outcomes system. Patients with PID and healthy volunteers aged ≥12 years, residing in Japan, and with access to a smartphone were eligible. HR-QOL (primary endpoint) was assessed by the EuroQol-5 Dimensions-5 Levels (EQ-5D-5L) and the Medical Outcomes Study 36-Item Short Form Health Survey (SF-36). Work productivity was assessed by the Work Productivity and Activity Impairment (WPAI) Questionnaire. Other aspects of PID and burden were assessed with a new questionnaire developed in-house. The study is registered at the University hospital Medical Information Network clinical trials registry (UMIN000045622). Results: The full interim analysis set comprised 71 patients with PID and 47 healthy volunteers. The most common International Union of Immunological Societies PID category was primary antibody deficiency (56.3% of patients). Complications were common, especially recurrent respiratory tract infections (63.4%). Most patients with PID were treated with immunoglobulin replacement therapy (73.2%); 22.4% of these patients had serum immunoglobulin levels <700 mg/dL. Among patients who did not undergo hematopoietic cell transplantation, EQ-5D-5L (n=67) and SF-36 (n=59) Physical and Mental Component Summary scores were significantly lower than in healthy volunteers (p < 0.001). WPAI absenteeism, work productivity loss, and activity impairment scores were significantly lower in 42 working patients with PID than in 37 working healthy volunteers (p < 0.05). Other results indicated that patients with PID experience substantial burdens related to medical visits, expenses, work, and daily activities. Discussion: This interim analysis confirms that patients with PID in Japan have lower HR-QOL and work productivity compared with healthy individuals and experience substantial limitations and burdens in their daily lives.